Mind games - Roberts, Nora (London Piatkus, 2024)
This wark is new thriller with tragedy and trauma, resilience and revenge..., Thea Fox is just twelve years old when her parents are brutally slain. With Thea's help the police are able to put their murderer - a psychotic serial killer called Ray Riggs - behind bars for life. Changed forever, Thea slowly learns to come to terms with the events of that terrible night and builds a new life in a small country town where she can breathe in the smells of pine, fresh bread and her grandmother's homemade candles. But the connection that helped Thea put her parents' killer behind bars will come to haunt her. Though her Grandmother calls it a gift, to Thea it feels more like a curse because Ray feels the connection too and though Thea may try to move on, Ray isn't willing to let her go quite so easily...
Keywords: Non Fiction; English Thriller